A cost - Ghahnavieh, Abbas Rajabi
Available transfer capability (ATC) is a measure of the transfer capability remaining in a transmission system. Application of unified power flow controllers (UPFCs) could have positive impacts on the ATC of some paths while it might have a negative impact on the ATC of other paths. This paper presents an approach to evaluate the impacts of UPFCs on the ATC from a cost/worth point of view. The UPFC application worth is considered as the maximum cost saving in enhancing the ATC of the paths due to the UPFC implementation. The cost saving is considered as the cost optimal application of other system reinforcement alternatives to reach the same ATC level obtained by UPFC application.
UPFC application costs include the maximum cost of alleviating the probable negative impact on the ATC of some paths caused by implementing UPFCs. Optimal system reinforcement is used for systems with UPFCs to determine the aforementioned cost. The proposed method is applied to the IEEE-RTS and the results are evaluated through a sensitivity analysis. The cost/worth of UPFC application is also used to develop an index for optimal UPFC location and the results are compared with those of other indices. A comparison is finally made with the results obtained using an existing ATC allocation profit-based approach to determine UPFC application worth.
Keywords: ATC enhancement; Unified power flow controller; Power system reinforcement